Fabrication of Heterogeneous TiO2-CdS Nanotubular Arrays on Transparent Conductive Substrate and Their Photoelectrochemical Properties - Jing Liu; Chenhui Meng; Zhaoyue Liu (Nanomaterials and Nanotechnology)
This paper describes an easy and time-saving strategy for the fabrication of heterogeneous nanotubular arrays of TiO2-CdS (TCHNTAs) on transparent conductive glass (FTO) and their photoelectrochemical properties. The use of transparent FTO instead of opaque Ti substrate allows incident light from the substrate side. The anodized TiO2 nanotubular arrays were firstly detached from Ti substrate by anodization under a high voltage of 120 V and then transferred to FTO substrate using TiO2 (P25) paste as a binder, followed by sensitization with CdS nanoparticles. After optimizing the deposition cycles of CdS nanoparti‐ cles, the TCHNTAs on FTO substrate demonstrated an enhanced photocurrent density in the Na2S/Na2SO3 electrolyte under front-side illumination from the FTO side, which improved by ~ 21% when compared with the photocurrent density under back-side illumination from the TiO2-CdS side. This improvement in photoelectrochem‐ ical properties can be ascribed to the reduced charge recombination on the interface between the TiO2 nanotubes and the CdS nanoparticles under front-side illumination. Our strategy for nanotubular transfer on transparent substrate may extend the applications of TiO2 nanotubular arrays into other fields, such as dye-sensitized solar cells, photochromism and photocatalysis.